2022
DOI: 10.3389/fonc.2022.892923
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Breast Cancer Radiotherapy Techniques Regarding Secondary Cancer Risk and Normal Tissue Complication Probability – Modelling and Measurements Using a 3D-Printed Phantom

Abstract: BackgroundRadiotherapy after breast-conserving therapy is a standard postoperative treatment of breast cancer, which can be carried out with a variety of irradiation techniques. The treatment planning must take into consideration detrimental effects on the neighbouring organs at risk—the lung, the heart, and the contralateral breast, which can include both short- and long-term effects represented by the normal tissue complication probability and secondary cancer risk.Patients and MethodsIn this planning study,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 84 publications
1
4
0
Order By: Relevance
“…There is also a risk of recurrence from the breast cancer metastasizing to another part of the body or increased susceptibility to a second primary cancer in a new location . Although subsequent cancers may arise due to chance, there is well-established evidence that certain types of breast cancer treatments, such as radiation therapy, result in an increased risk of secondary cancer and damage to surrounding tissues …”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…There is also a risk of recurrence from the breast cancer metastasizing to another part of the body or increased susceptibility to a second primary cancer in a new location . Although subsequent cancers may arise due to chance, there is well-established evidence that certain types of breast cancer treatments, such as radiation therapy, result in an increased risk of secondary cancer and damage to surrounding tissues …”
Section: Introductionsupporting
confidence: 83%
“…6,7 Although subsequent cancers may arise due to chance, there is well-established evidence that certain types of breast cancer treatments, such as radiation therapy, result in an increased risk of secondary cancer and damage to surrounding tissues. [8][9][10] The role of radiation therapy in subsequent cancer development has been studied for a range of primary cancers, including those of the prostate and rectum, 11 head and neck, 12 and breast. 13 Much of the literature focuses on secondary lung cancer or cardiovascular disease risk after breast cancer radiation therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To be noted, there are few existing NTCP models tailored for BC radiotherapy, and generally, they are obtained from photon therapy cohorts, 42 44 which brings up questions about the applicability of photon NTCP models to PT. Blanchard et al verified that in patients with head and neck cancer (HNC), the accuracy of NTCP model based on photon therapy data decreased in PT, but the diversity was within the acceptable range.…”
Section: Potential Approaches For Patient Selectionmentioning
confidence: 99%
“…[ 12 18 19 20 21 22 ] Several authors have measured doses of in-field and out-of-field organs in physical phantoms with passive detectors and compared their results with the TPS results. [ 8 12 21 22 23 24 25 ] All the investigators reported that the TPS cannot calculate the out-of-field dose accurately and the gold standard method to estimate this dose is MC simulation based on a patient’s DICOM data or using computational phantom. [ 12 17 26 27 28 29 ] Bednarz et al .,[ 26 ] Joosten et al .,[ 16 ] Berris et al .,[ 27 ] and Wang and Ding (2014)[ 30 ] evaluated the out-of-field dose calculated by different TPS and used the MC simulation to estimate the uncertainties of calculated organ doses.…”
Section: Introductionmentioning
confidence: 99%